2010
DOI: 10.1007/s00261-010-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound ablation in hepatic and pancreatic cancer: complications

Abstract: The complications of HIFU develop mainly around the targeted lesions or along the ultrasound beam pathway. It is essential to have awareness of the possible complications related to HIFU and its imaging features for to avoiding serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 19 publications
3
95
1
Order By: Relevance
“…[6][7][8][9] Histotripsy uses cavitation, which is a threshold phenomenon. When acoustic pressure perturbations within the focal volume of the transducer are large enough (ie, negative pressure swings sufficiently low), cavitation will occur.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Histotripsy uses cavitation, which is a threshold phenomenon. When acoustic pressure perturbations within the focal volume of the transducer are large enough (ie, negative pressure swings sufficiently low), cavitation will occur.…”
Section: Discussionmentioning
confidence: 99%
“…Planned iatrogenic right hydrothorax with intra-pleural infusion of warm saline solution was reported in 272 cases, to enhance HIFU coupling in cases of liver dome tumor (26,35,36,38,41,45,52,55,75). Other studies reported on the use of artificial pleural infusion or artificial ascites in selected cases, without detailing the number of patients (42)(43)(44)49,51).…”
Section: Records Included For Qualitative Synthesis N=67mentioning
confidence: 99%
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…However, as reported in previous studies, HIFU induced skin burns and pain in the treatment region, neurapraxia of stomach and intestines, rarely developed superior mesenteric infarction and perforation in terminal ileum [4]. Jung et al [5] showed that the ultrasound heat could cause third-degree burn, necrosis of the ribs along the main ultrasound beam path, rib fractures and other complications such as biliary obstruction, pneumothorax and fistula formation.…”
Section: Introductionmentioning
confidence: 79%